A fuzzy linear programming enterprise input–output model for optimal crisis operations in industrial complexes - Tan, Raymond Girard R. (Animo Repository, 2016)
Industrial complexes may be subject to significant risk of cascading failure caused by various disruptions and emerging economies are potentially more susceptible to the impacts as less established policies are in place to deal with these issues. In particular, there is a need to develop adaptation strategies to ensure the resilience of industrial activities to various perturbations that may result from climate change. The inherent complexity of such systems makes decision-making for risk management a non-trivial task that is best facilitated with the aid of mathematical models. Enterprise input–output models have been used extensively to model production systems at different scales. In this work, a fuzzy linear programming enterprise input–output model is developed to determine optimal adjustments in production levels of multi-product systems when a crisis is induced by a loss of resource inputs. The model allows for adjustments that are equitable for different decision-makers that may comprise an industrial complex or a supply chain. Capabilities of the model are illustrated with a case study on the effect of water shortage on an aluminum production system. © 2015 Elsevier B.V.